(Im)permanence of Polish Constitutionalism: in Search of an Optimal Vision of the State - Lis-Staranowicz, Dorota; Dobrowolski, Marek (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
Poland is a state where the elites’ strong attachment to the idea of a written constitution prevails, as evidenced by the special place held by the Government Act of 3 May 1791 in political and academic discourse. The constitutional awareness of the citizens is also growing year after year as they are increasingly reliant on the provisions of the current Constitution of 2 April 1997, seeking the protection of their rights and freedoms before the courts. However, the period between 1791 and 1997 is not a constitutional vacuum. At that time, although as many as eight Basic Laws1 were applicable on Polish lands, some of them were imposed on Poles against their will. In total, the ‘mathematical’ balance of constitutional experience, simplified to some extent, is as follows: 10 constitutional acts are attributable to a period of 206 years (counting from the adoption of the oldest until the adoption of the youngest Constitution); thus, the average lifespan of each of them is 20 years and 7 months. If we change the frame of reference and consider the period between 1791 and 2021, the average validity of the constitution on Polish lands increases to 23 years. If only the validity of individual Basic Laws is taken as a reference, the average decreases to approximately 12 years. In political practice, as discussed below, Polish constitutions were created slowly but quickly collapsed.KEYWORDS: constitutionalism, constitutional history, transition, independence.